PENERAPAN MODEL PEMBELAJARAN KOOPERATIF PENDEKATAN STRUKTURAL THINK PAIR SQUARE (TPS) UNTUK MENINGKATKAN HASIL BELAJAR MATEMATIKA SISWA KELAS VIIG SMP NEGERI 1 SIAK HULU - Wati, Vina Erna; Kartini, Kartini; Zulkarnain, Zulkarnain (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2019)
Abstract: This research is classroom action research (PTK) which aims to improve the learning process and improve mathematics learning outcomes by applying the cooperative learning model Think Pair Square (TPS) approach. This research consists of two cycles, each of which has four stages, namely planning, implementation, observation, and reflection. Subjects were class VIIG students of SMP Negeri 1 Siak Hulu in the even semester of the 2018/2019 academic year as many as 32 people, 16 male students and 16 female students. The instruments of data collection are observation sheets and tests of mathematics learning outcomes. The observation sheet was analyzed qualitatively descriptive, while the mathematics learning outcomes test was analyzed quantitatively descriptive statistics. Qualitative analysis shows that there is an improvement in the learning process from before action to cycle I and cycle II. Students are seen to be actively participating and increasingly independent in the learning process carried out, such as in solving mathematical problems given, presenting the results of problem solving and providing learning conclusions. Quantitative analysis shows that the number of students who achieved knowledge KKM increased from the base score (28.12%) to UH I (40.62%) to UH II (56.25%). For skills from UH I (28%) to UH II (62.5%). The results of this study indicate that the application of the cooperative learning model Think Pair Square (TPS) approach can improve the learning process and improve the mathematics learning outcomes of students in VIIG class 1 Siak Hulu Public Middle School 2018/2019 in the subject matter of Social Arithmetic.Key Words : Mathematics Achievement, Learning Cooprative Approach Think Pair Square (TPS)